EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS GOOGLE EARTH TERHADAP PEMAHAMAN SPASIAL SISWA DALAM PEMBELAJARAN SEJARAH - Rahmawati, Dina; Sriwati; Mardiani, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students' spatial understanding in history learning remains suboptimal, particularly in recognizing the geographical location of events, determining direction and distance, and explaining relationships between regions in historical contexts. This study aims to describe the use of the Google Earth application in history learning, to compare the level of students' spatial understanding between the experimental and control classes, and to examine the effect of using Google Earth on the spatial understanding of grade X students at SMK Negeri 2 Banjarmasin. A quantitative approach with a Quasi-Experimental Nonequivalent Control Group Design was employed, involving an experimental class (Google Earth) and a control class (short video), each consisting of 34 students selected through purposive sampling. Data were collected through pretest and posttest instruments that had been tested for validity, reliability, difficulty level, and discriminating power, then analyzed using descriptive statistics, normality tests, N-Gain Score, and the Mann-Whitney U test. The results show that the implementation of Google Earth in history learning ran well. The experimental class's mean score increased from 16.09 to 17.70 (N-Gain 0.23, low category), while the control class increased from 15.92 to 17.37 (N-Gain 0.35, moderate and more stable category). The Mann-Whitney U test (Asymp. Sig. = 0.146 > 0.05) indicated no statistically significant difference between the two classes, mainly due to limited learning time that increased students' cognitive load while learning to operate a new application. Nevertheless, Google Earth qualitatively provided a more interactive and contextual learning experience. It is concluded that Google Earth has the potential to become an effective history learning medium when supported by sufficient time allocation and combined with other appropriate learning media.